Answer :

Given that,



Now,


f(-1) = 3(-1) = -3 [since -1<1 and f(x) = 3x for x≤ 1]


f(2) = 22 = 4 [since 2<3 and f(x) = x2 for 1<x≤ 3]


f(4) = 2(4) = 8 [since 4>3 and f(x) = 2x for x>3]


f (– 1) + f (2) + f (4) = -3+4+8 = 9

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar